ÓSPIRIMLIK DAWIRDE OYLAW PROCESINIŃ RAWAJLANÍW ÓZGEShELIKLERI - Djolımbetova, M.M. (SCIENCE and SOCIETY, 2025)
This state presents information about the psychological differences of adolescence, the development of the thought process and independent thinking, mixing, as well as the study and analysis of the thought process in various literature.